Incidence of MRSA at admission to an acute hospital in Ireland - a four year prospective study - Higgins, Ann; Gethin, Georgina; Lynch, Maureen (International Journal of Infection Control, 2010)
There is a paucity of information on the prevalence of MRSA at admission to Irish hospitals yet the Department of Health and Children (DOHC) recommends admission screening of patients considered to be at increased risk of MRSA. This study aimed to determine the prevalence of MRSA at admission to one Irish hospital and make comparisons with national and international rates. Rates of MRSA colonisation were determined by taking swabs from a minimum of three body sites at the time of admission to the hospital. Screening was targeted to all patients for high risk surgery and other patients considered at increased risk of MRSA colonisation as per international guidelines. Prevalence varied depending on speciality and patient's age. Patients aged over 70 were twice as likely to be colonised with MRSA than those under 70 (OR 2.004, p<0.000001). Patients over 80 years were 2.5 times more likely to be colonised with MRSA (OR 2.52, p<0. 00001)This study provides valuable data on the overall prevalence of MRSA in at risk patients admitted to an Irish Hospital.